Meta-Analysis: The Effectiveness of Web-Based Health Promotion Interventions on Vegetable Consumption in Children - Sinar Perdana Putra; Yulia Lanti Retno Dewi; Bhisma Murti (Journal of Health Promotion and Behavior, 2020)
Background: Consuming healthy food throughout life helps prevent malnutrition in all forms of various diseases. In the first 2 years of a child's life, optimal nutrition fosters healthy growth. Vegetables and fruit are food sources that contain many nutrients that humans must consume at every meal. EHealth is playing an increasingly large role in life and the internet has great potential to be a source of low cost and effective health promotion interventions.Subjects and Method: This study was a meta-analysis of a number of Randomized Controlled Trial study designs. The articles used in this study were obtained from several databases including PubMed, Google Scholar, and Springer Link. The articles used in this research are those published from 2010-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. The population in the study was children aged 2 to 12 years old with an intervention in the form of web-based health promotion, comparison, which was not given a web outcome-based health promotion intervention in the form of vegetables consumption. The keywords for finding articles are as follows: "Intervention Health Promotion Web-Based" OR "eHealth Intervention" AND "Non-Intervention Health Promotion Web-Based" OR "Non eHealth Intervention" AND "Child" AND "Vegetables" AND "Randomized Controlled Trial”. The articles included in this study were full text articles with the design of a Randomized Controlled Trial (RCT) study. Articles were collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 9 articles were reviewed in this study. Meta-analysis of 9 primary data shows that web-based health promotion interventions can increase children's vegetable consumption with statistically significant results (Standarized Mean Difference= 0.82; 95% CI= 0.26 to 1.37; p= 0.004).Conclusion: Web-based health promotion interventions can increase vegetables consumption in children.Keywords: Intervention Health Promotion Web-Based, eHealth, vegetables consumptionCorrespondence: Sinar Perdana Putra. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: perdanasinarp@gmail.com Mobile: 085727777227.Journal of Health Promotion and Behavior (2020), 05(03): 197-208https://doi.org/10.26911/thejhpb.2020.05.03.06.